Metabolic and Hematologic Synergism in Idiopathic Intracranial Hypertension: Reversal of Bilateral Papilledema via Multidisciplinary Gynecological and Systemic Interventions - Anak Agung Putri Satwika; Anak Agung Mas Putrawati Triningrat; Made Widhi Asih (HM Publisher, 2026)
Background: Idiopathic Intracranial Hypertension (IIH) conventionally presents with elevated intracranial pressure without structural etiologies, heavily associating with central adiposity. Emerging clinical frameworks recognize the intersecting roles of hematologic and metabolic abnormalities, notably iron deficiency anemia and hypovitaminosis D. Case presentation: A 41-year-old obese female (Body Mass Index 30.04 kg/m2) presented with progressive, painless bilateral visual blurring. Initial evaluation revealed a right eye visual acuity of 6/7.5 and a severely reduced left eye visual acuity of 1/60, alongside prominent bilateral papilledema and flame-shaped hemorrhages. The patient was incorrectly diagnosed with optic neuritis externally. Upon referral, rigorous evaluation successfully dismantled the misdiagnosis; intact pupillary reflexes, absence of a relative afferent pupillary defect, and an enlarged blind spot pointed definitively to papilledema. A lumbar puncture confirmed an elevated opening pressure of 340 mmH2O with normal cerebrospinal fluid composition. Targeted systemic profiling uncovered severe iron deficiency anemia (Hemoglobin 7.90 g/dL) driven by chronic menorrhagia from a uterine myoma, compounded by marked hypovitaminosis D. A tailored multidisciplinary intervention was initiated. A conservative acetazolamide dosage (500 mg/day) was utilized to minimize systemic stress, combined with cholecalciferol supplementation, ferrous sulfate, and a laparotomic myomectomy. One month post-operatively, hemoglobin normalized to 11.70 g/dL, visual acuity was fully restored to 6/6 bilaterally, and papilledema completely resolved. Conclusion: IIH is a multifactorial systemic syndrome. Prompt identification and aggressive correction of hematologic and metabolic drivers, including surgical eradication of hemorrhagic etiologies, are imperative for reversing intracranial hypertension and preventing permanent optic neuropathy.